Sensitive surfactant-mediated spectrofluorimetric determination of sildenafil - Wang, Chien Chun (2010)
Two simple and sensitive surfactant-mediated spectrofluorimetric methods for the determination of sildenafil are proposed in this paper. These methods are based on the interaction of sildenafil with normal micelles of HTAB (hexadecyltrimethylammonium bromide, method A) and the formation of ion-association complexes of sildenafil with SDS (sodium dodecyl sulfate, method B). In both methods, the formed species produce considerable fluorescence enhancement, which allows sildenafil to be quantitatively determined. Linearity was obtained for sildenafil in the concentration range 0.004 to 25 μg mL -1 with a detection limit of 0.0012 μg mL-1 by method A; and a linearity range of 0.005 to 50.0 μg mL-1 with a detection limit of 0.0016 μg mL-1 by method B. The proposed methods have been applied to the analysis of bulk drug, tablets, herbal medicine and beverages. Validation processes were performed by recovery studies and statistical analysis with satisfactory results.